2021
DOI: 10.1016/j.resp.2021.103644
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function and functional capacity in COVID-19 survivors with persistent dyspnoea

Abstract: The purpose of this study was to examine the physiological mechanisms of persistent dyspnoea in COVID-19 survivors. Non-critical patients (n = 186) with varying degrees of COVID-19 severity reported persistent symptoms using a standardized questionnaire and underwent pulmonary function and 6-minute walk testing between 30 and 90 days following the onset of acute COVID-19 symptoms. Patients were divided into those with (n = 70) and without (n = 116) persistent dyspnoea. Patients with persistent dyspnoea had sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
17

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(127 citation statements)
references
References 16 publications
6
104
0
17
Order By: Relevance
“…Participants reporting use of medications for autoimmune disease reported a median [IQR] of 7 [5][6][7][8][9] symptoms at enrollment, while the median [IQR] number of symptoms for all other participants was 7 [4][5][6][7][8][9]. The median [IQR] severity score at enrollment for those reporting use of medications for autoimmune disease was 12 [7][8][9][10][11][12][13][14][15][16][17] decreased sense of smell or taste at enrollment; among those reporting use of medications for autoimmune disease, a higher proportion reported symptoms at all time points in follow-up, as well as symptoms of greater severity (Figure 1). Around day 30 (range=24-45 days) a higher proportion of participants reporting use of medications for autoimmune disease remained symptomatic compared to all other participants, with 67% vs 34% continuing to report fatigue, 40% vs 19% reporting nasal congestion, 33% vs 20% cough, and 33% vs 12% shortness of breath (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants reporting use of medications for autoimmune disease reported a median [IQR] of 7 [5][6][7][8][9] symptoms at enrollment, while the median [IQR] number of symptoms for all other participants was 7 [4][5][6][7][8][9]. The median [IQR] severity score at enrollment for those reporting use of medications for autoimmune disease was 12 [7][8][9][10][11][12][13][14][15][16][17] decreased sense of smell or taste at enrollment; among those reporting use of medications for autoimmune disease, a higher proportion reported symptoms at all time points in follow-up, as well as symptoms of greater severity (Figure 1). Around day 30 (range=24-45 days) a higher proportion of participants reporting use of medications for autoimmune disease remained symptomatic compared to all other participants, with 67% vs 34% continuing to report fatigue, 40% vs 19% reporting nasal congestion, 33% vs 20% cough, and 33% vs 12% shortness of breath (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the odds of experiencing persistent fatigue and shortness of breath at approximately 30 days were included as outcomes of special interest, as those symptoms are commonly reported as having a significant impact on the ability to perform daily living and work activities; [6][7][8][9] persistent shortness of breath may also indicate long-term damage to the lungs. 10 Potential confounders included in all models were demographics and risk factors for more severe COVID-19 disease: age in 10-year intervals, gender, race, ethnicity, body mass index (BMI) category, level of education, smoking status, use of medications for diabetes, hypertension, or lung disease. Models for 30-day symptom persistence were additionally adjusted for the number of symptoms reported at enrollment to account for differential reporting patterns (eg, those reporting more symptoms at enrollment might also report more symptoms in follow-up).…”
Section: Methodsmentioning
confidence: 99%
“…As the lungs are a primary target for COVID-19, with varying degrees of impact, newly developed COPD after infection was documented in 10 (1.8%) patients, and 17 more (60.7%) required treatment intensification. The physiological mechanisms leading to persistent dyspnea in non-critically ill COVID-19 survivors have been recently analyzed [54], and a significant decrease in forced vital capacity (FVC), forced expiratory volume in the first second (FEV1), and diffusing capacity of the lung of carbon monoxide (DLCO) after 6 min' walking distance was noted among patients with persistent dyspnea when examined 30-60 days after the onset of COVID-19 symptoms. The respiratory outcomes in SARS and MERS-the two previous viral infection outbreaks similar to COVID-19-were systematically reviewed: after 12 months, 32.4% of sufferers who recovered presented impaired FEV1, and 29.8% had a decrease in FVC [55], which parallels the 22.6% functional impairment documented in COPD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Even after six months, lower DLCO and TLC were detected in patients with critical disease [19]. A Mexican study investigating the correlation between persistent dyspnoea and pulmonary function reported that patients with persistent dyspnoea had significantly lower FVC, FEV1 and DLCO values than those without [21].…”
Section: Discussionmentioning
confidence: 99%